Kantian Disregard for Non-Rational Humans: Immanuel Kant’s Haunting Impact on Contemporary Bioethics - Six, Jay (Stance: an international undergraduate philosophy journal, 2022)
I seek to emphasize Immanuel Kant’s lingering and unsavory impact on medical ethics by emphasizing Kantian ethics’ disregard for non- rational humans. We must be considerate when discussing individuals who have some form of dementia, conditions that irreversibly diminish the ability to use rational thought, sometimes to a degree of severity that hinders essential daily functions. I argue that to consider ourselves proponents of human equality we must treat humans with dementia as members of the kingdom of ends.